تسويق البحث العلمي بالأكاديمية الليبية فرع مصراتة من وجهة نظر أعضاء هيئة التدريس العاملين بها (Economic studies journal, 2023)
The research aimed to identify the reality of marketing scientific research at the Academy Libyan - Misurata , as well as knowledge of the obstacles facing the marketing of scientific research in the Libyan Academy- Misrata , and the research community consisted of all members of the teaching staff affiliated with the Academy- Misurata , and their number reached (45) members, and the descriptive approach was used, and through the questionnaire , the research data was collected.of the research showed that there is a decline in the marketing of scientific research in the Libyan Academy, the Misurata branch , as well as c and d obstacles facing the marketing of scientific research in the Libyan Academy, the Misurata branch .
Keywords: Scientific research; scientific research marketing, scientific research marketing obstacles